Dzimtene un identitātes meklējumi Mahmuda Darviša dzejā - Alieva, Aibaniz (Latvijas Universitāte, 2023)
Aim: The aim of this bachelor thesis is to explore the themes of homeland and identity in the poetry of Mahmoud Darwish, a renowned Palestinian poet. By analyzing selected poems, the thesis seeks to understand the complex relationship between Palestinians and their homeland, as well as the ways in which Darwish's poetry captures and communicates the Palestinian experience of displacement, longing for homeland, and resistance. Main conclusions: Homeland and the search for identity are central themes in Darwish’s work. Poems reflect the complex interplay between personal and collective identities, marked by the lived realities of occupation and displacement. Darwish uses the Palestinian to evoke the sense of belonging to their homeland, construct collective identity and create a metaphorical homeland for his people in his works. Structure of the work: This thesis is divided into three main chapters. First chapter describes Mahmoud Darwish’s life, historical background, and his literary influences. Second chapter examines concept of homeland, identity, and the role of poetry in shaping collective identity within Palestinian context. Third chapter addresses the concepts of homeland and identity in the poetry of Mahmoud Darwish and provides the analysis of six poems.
Homeland and Search for Identity in the Poetry of Mahmoud Darwish
Keywords: Āzijas studijas; Mahmoud Darwish; homeland; identity; poetry; exile